2015
DOI: 10.1227/01.neu.0000462076.73701.09
|View full text |Cite
|
Sign up to set email alerts
|

The Comprehensive Anatomical Spinal Osteotomy Classification

Abstract: This proposed anatomically based classification system provides a consistent description of the various osteotomies performed in spinal deformity correction surgery. The reliability study confirmed that the classification is simple and consistent. Further development of its use will provide a common frame for osteotomy assessment and permit comparative analysis of different treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(56 citation statements)
references
References 14 publications
0
54
0
2
Order By: Relevance
“…The second technique disseminated in the literature in recent years is the posterior vertebral column resection (pVCR), published by Suk et al 5 This technique has lower morbidity because of its use of a single access, through which Schwab grade V or VI 6 vertebral body osteotomies at the apex of the curve can be performed, which permits good correction of the deformity through this region, but generates at this point an area of high instability that increases the risk of accidental spinal cord lesion during the execution of the correction maneuvers. Scoliosis is corrected mostly through this region, with two rigid blocks remaining proximal and distal to the apical region.…”
Section: Introductionmentioning
confidence: 99%
“…The second technique disseminated in the literature in recent years is the posterior vertebral column resection (pVCR), published by Suk et al 5 This technique has lower morbidity because of its use of a single access, through which Schwab grade V or VI 6 vertebral body osteotomies at the apex of the curve can be performed, which permits good correction of the deformity through this region, but generates at this point an area of high instability that increases the risk of accidental spinal cord lesion during the execution of the correction maneuvers. Scoliosis is corrected mostly through this region, with two rigid blocks remaining proximal and distal to the apical region.…”
Section: Introductionmentioning
confidence: 99%
“…21 These techniques involve Grade 3-5 resections and encompass pedicle subtraction osteotomies (PSOs), vertebral column resections (VCRs), and kyphectomies. When purely posteriorly based, 3COs involve resection of pedicles and a portion of or the entire vertebral body, as well as the possibility of intervertebral disc removal.…”
mentioning
confidence: 99%
“…2,4 Their use is only justified because sagittal correction is of great importance in the context of adult deformities, since it has been shown that pain and disability are directly related to an increased SVA and changes in sagittal spinopelvic parameters. [13][14][15] When considering a three-column osteotomy, the decision making process should take the possibility of not achieving sufficient correction or of having postoperative loss of correction into account, [5][6][7][8] since the procedure is subject to various complications and mechanical failures, and may also be impacted by reinterventions that may occur. 16 However, this point is addressed by few articles, which usually originate in centers of excellence where osteotomy procedures have been developed and perfected, and it is not reasonable to expect the technique to spread to smaller centers.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid confusion with the various nomenclatures present in the literature, the types of osteotomies performed were described as grade three, four, or five, according to the classification of Schwab et al 7 ( Figure 1) Only those cases that presented SVA ≤ 5cm, PI-LL ≤ ± 10˚, and PT ≤ 24˚8 -12 were considered to be ideal corrections. Loss of correction was defined as any angular variation greater than 5˚ or an increase in SVA of 2cm or more.…”
Section: Methodsmentioning
confidence: 99%